Removing situation descriptions from situational judgment test items: Does the impact differ for video‐based versus text‐based formats? - Schäpers, Philipp; Lievens, Filip; Freudenstein, Jan‐Philipp; Hüffmeier, Joachim; König, Cornelius J.; Krumm, Stefan (Journal of occupational and organizational psychology, 2020)
Recent research has shown that many text‐based situational judgment test (SJT) items can be solved even when the situational descriptions in the item stems are not presented to test takers. This finding challenges the traditional view of SJTs as low‐fidelity simulations that rely on ‘situational’ (context‐dependent) judgment. However, media richness theory and construal level theory suggest that situation descriptions presented in a richer and more concrete format (video format) will reduce uncertainty about inherent requirements and facilitate the perception that the situation is taking place in the here and now. Therefore, we hypothesized that situational judgment would be more important in video situation descriptions than in text situation descriptions. We adapted a leadership SJT to realize a 3 (situation description in the item stem: video vs. text vs. none) × 2 (response format: video response options vs. text response options) between‐subjects design (N = 279). Participants were randomly assigned to one of the six conditions. The removal of video‐based situation descriptions in item stems led to an equivalent decrease in SJT scores as the removal of text‐based situation descriptions in item stems (video‐based version: Cohen's d = 0.535 vs. text‐based version: Cohen's d = 0.531). SJT scores were also contingent on the presentation format of both situation descriptions and response options: The highest scores were observed when situation descriptions and response options were presented in the same format. Implications for SJT theory and research are discussed. Practitioner points The presentation format did not moderate the effect of omitting situation descriptions in SJTs – that is, the context dependency of SJT performance did not increase when the SJT was administered in a video‐based rather than a text‐based format. The elimination of situation descriptions in item stems had a medium effect on overall test scores: SJT scores were significant lower without situation descriptions in comparison to SJT scores with situation descriptions (video‐based version: Cohen's d = 0.535 vs. text‐based version: Cohen's d = 0.531). It is important to match the stimulus and response formats in SJTs.